Credit Unions and Co-operative Banks Across the World - Goglio, Silvio; Kalmi, Panu (Oxford University Press, 2017)
The national cases of co-operative banking will be considered by pattern: credit unions (as in the UK and the US), decentralized networks (as in Germany, Italy, and Austria), and centralized networks (as in France, the Netherlands, and Finland). The analysis will consider the historical evolution that has characterized the different patterns with regard to national peculiarities (social and economic). We also discuss performance measurement in financial co-operatives and how the recent economic and financial crises have impacted their success vis-à-vis shareholder banks. We also consider corporate governance and regulatory challenges facing financial co-operatives. The present process of hybridization in the sector will also be taken into consideration as well as relaunched co-operatives in the twenty-first century.
Keywords: co-operative banks; credit unions; co-operative networks; bank performance; corporate governance; banking regulation; fi=Taloustiede|en=Economics|